Black lives matter: from a moment to a movement - Hillstrom, Laurie Collier (Greenwood, an imprint of ABC-CLIO, LLC, 2018)
Historical roots of the movement -- The origin of #BlackLivesMatter -- From social media to the streets of Ferguson -- The movement gains force -- The role of social media -- Criticism and backlash -- Racial injustice in America